Empirical analysis of social impacts of a rural social enterprise: insights for local and regional development - Peter Musinguzi; Renato A. Villano; Derek Baker (Regional Studies, Regional Science)
In developing countries the most marginalised and disadvantaged people are in rural, remote and regional areas and social enterprises in these areas – rural social enterprises (RSEs) – have been identified as key development actors in this context. However, their impacts are rarely rigorously measured. Our study fills this gap by measuring an RSE’s social impact in a developing country. A smallholder farmers’ survey (n = 1021) is utilised in a propensity score-based method which allowed us to generate counterfactual and estimate outcomes between members and non-members of an RSE. This method was complemented by a stakeholder focus group discussion. Predictors of participation and social impacts of the RSE are identified besides an evaluation of its interventions. Results generate implications for social enterprise practitioners, supporters and policymakers interested in applying RSEs as local and regional development actors as well as researchers involved in social impact measurement.